Acute progressive large-area cerebral infarction caused by wasp sting: a case report. Issue 4 (4th July 2022) - Min, Liu; Wenning, Zhang; Wei, Wang; Wei, Wang
ABSTRACT: Acute renal failure, multiple organ failure, and allergic reactions caused by wasp sting have been reported in many clinical reports, however, there are few reports on cerebral infarction due to wasp sting. We report a patient who developed acute progressive cerebral infarction after wasp stings, suffered from left-sided hemiplegia, clumsy speech, and left facial droop, only left the MRC grade 2 power and left conjugate gaze palsy after treatment. The MRA showed normal blood vessels. And the wasp sting was detected in head and right shoulder. We explored the mechanism by which the bee venom induced vasospasm and stimulated the superior cervical sympathetic ganglion leading to cerebral infarction. The treatment strategy is presented to provide experience for other clinicians.